(untitled) - Yamashita, Toshihiko (Tokyo, 1989)
This book introduce the early days, the big-ness syndrome, the changing face of business. Adversity builds character. Operating in the world economy and a second life.
Keywords: Công nghiệp điện,Electric industries; Lịch sử,History; Nhật Bản,Japan